PRODUKSI SERASAH DAUN TUMBUHAN EHA (Castanopsis buruana Miq.) DI KAWASAN HUTAN LINDUNG NANGA-NANGA PAPALIA PROVINSI SULAWESI TENGGARA - Muhsin Muhsin; Indrawati Indrawati; Nur Insani (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2015)
ABSTRACT The aims of this study was to know the litter production of Eha leaves (Castanopsis buruana Miq.) at Nanga-Nanga Papalia protected forest Southeast Sulawesi province. The method that use was litter trap methods with 3 plot establish at study site based on presentage of crown covering. The litter drainage using oven with temperature ± 85ºC to 24 hours. The result of this study showed that litter production of Eha leaves (Castanopsis buruana Miq.) during 4 time of observation showed that the highest average total of litter production on plot I was 55,72 g/m2/weeks, 62,2 g/m2/weeks, 103,3 g/m2/weeks and 104,33 g/m2/weeks. Plot II was 38,10 g/m2/weeks, 41,28 g/m2/weeks, 73,44 g/m2/weeks and 71,73 g/m2/weeks. Plot III 47,47 g/m2/weeks, 49,21 g/m2/weeks, 66,15 g/m2/weeks and 65,19 g/m2/weeks. The mounthly litter production of eha leaves (Castanopsis buruana Miq.) highest on April was 968,29 g/m2/mounth and the lowest on March was 588 g/m2/mounth.Keywords : Litter, Eha (Castanopsis buruana Miq.), Nanga-Nanga Papalia.